Economic Policy and Analysis of the Draft Forcast by the Ministry of Economic Development of the Russian Federation Up to 2024 - R. S. Dzarasov; G. P. Zhuravleva; E. V. Aleksandrova (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
Topicality of the document prepared by the Ministry of Economic Development of the Russian Federation -the Forecast of the Social and Economic Development of the Russian Federation up to 2024 (hereafter referred to as the MED Forecast) implies both estimation of principle factors, which can affect the development of economy in the country within the set period and at the same time demonstration of the potential effect of steps planned by the government. The article shows that it is the draft of the forecast and of the strategy of the country development. The authors think that the document shall be reviewed as a proposal, where key factors of economy will be budget rule execution, i.e. fixing long-term restrictions on budget policy indicators; investment in the fixed capital attended by certain measures of the government aimed at creating conditions for their growth; monetary and credit policy providing economic development stability; pension reform connected with the supposed improvement on labour market. Methodological foundation of the research was formed by a number of academic methods, such as observation and collection of facts, modeling, analysis and synthesis, system approach, induction and deduction, historic and logical methods. It is a combination of modes that are used for comprehensive characteristic of phenomenon and process development through digital data. Nature of set tasks determined the necessity to apply such method as the archive search and the comparative method.